The Efect of Work Life Balance on Turnover of Employees with Job Satisfaction Mediation (Study at PT. Ruang Raya Indonesia “Ruangguru.com”) - Asha Insan Pratama; Eeng Ahman (Budapest International Research and Critics University, 2023)
This research was conducted to analyze the effect of work life balance on employee turnover with job satisfaction as a mediating variable. The method used in this study uses a quantitative method with a descriptive approach and the data obtained is primary data by distributing questionnaires and secondary data obtained from the company. Based on the data obtained, it can be seen that the phenomenon is the turnover rate at PT. Ruang Raya Indonesia which is caused by work life balance problems by increasing job satisfaction must be further investigated to find a solution so that it is not in the high category.